Antioxidant activity of Maillard reaction products (MRPs) in a lipid-rich model system. (1st October 2016) - Vhangani, Lusani Norah; Van Wyk, Jessy
Highlights: Maillard reaction products (MRPs) exhibit peroxyl and DPPH radical scavenging activity. The antioxidant activity of MRPs varies with reaction temperatures, time and molecular weight fraction. Maillard reaction products inhibit lipid oxidation. Maillard reaction products exhibit antioxidant activity comparable to BHA. Abstract: Ribose-lysine (RL), ribose-glycine (RG), fructose-lysine (FL) and fructose-glycine (FG) Maillard models (whole mixture (WM) pH 4 and 9) were heated at 60, 80, 121 °C for 30, 60, 120 min, and dialysed into low (LMW) and high molecular weight (HMW) fractions. Reducing power (RP), DPPH and peroxyl radical scavenging (PRS) evaluated indirect antioxidant activity (AA). Direct AA in a water-in-oil emulsion was evaluated through peroxide value (PV), p -anisidine, TBARs inhibition and oxidative stability (OS). PRS and RP increased significantly with temperature and time from FL < FG < RL < RG and LMW < WM < HMW for all pHs. MRPs showed higher PRS and RP than BHA. DPPH decreased ( p  < 0.05) with temperature and time from LMW > WM > HMW. With DPPH, only MRPs at 121 °C exhibited higher AA than BHA. MRPs exhibited low PV, p -anisidine and inhibited the formation of TBARs. BHA showed the highest OS, with p -anisidine, PV and inhibition of TBARS similar to that of MRPs.